2004
DOI: 10.1196/annals.1318.005
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Circulating Microsatellite‐DNA in Blood of Patients with Breast Cancer

Abstract: Increased levels of circulating DNA have been reported in the blood of cancer patients but not healthy individuals. Tumor-specific genomic aberrations, such as loss of heterozygosity (LOH) and microsatellite instability (MSI), can be detected in this free extracellular DNA. Identification of these genetic aberrations may play an important role in cancer diagnosis and prediction of disease progression. Moreover, the genomic regions involved might harbor potential targets for therapies. To evaluate the incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 18 publications
(18 reference statements)
0
29
0
4
Order By: Relevance
“…Koyanagi et al showed that the detection of CTC was correlated with tumour-related methylated DNA and that a combined assessment of both molecular markers improved the assessment of prognosis in stage IV melanoma patients treated with biochemotherapy. However, Schwarzenbach et al did not observe a correlation between the incidence of loss of heterozygosity in circulating DNA and the presence of CTC in the blood from breast cancer patients (Schwarzenbach et al, 2004). The observed correlation between CTC and circulating methylated DNA in our study could be interpreted in two ways: (a) CTC are a potential source of circulating tumour-specific DNA; (b) high numbers of CTC and circulating methylated DNA are both a phenotypic feature of more aggressive tumour biology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Koyanagi et al showed that the detection of CTC was correlated with tumour-related methylated DNA and that a combined assessment of both molecular markers improved the assessment of prognosis in stage IV melanoma patients treated with biochemotherapy. However, Schwarzenbach et al did not observe a correlation between the incidence of loss of heterozygosity in circulating DNA and the presence of CTC in the blood from breast cancer patients (Schwarzenbach et al, 2004). The observed correlation between CTC and circulating methylated DNA in our study could be interpreted in two ways: (a) CTC are a potential source of circulating tumour-specific DNA; (b) high numbers of CTC and circulating methylated DNA are both a phenotypic feature of more aggressive tumour biology.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible sources include DNA leakage from cells as the result of tumour necrosis or apoptosis, or spontaneous release of DNA into the circulation from primary and metastatic tumours (Stroun et al, 2000). Although many studies have suggested the usefulness of CTC or cell-free DNA as a surrogate marker of subclinical metastasis for breast cancer (Taback et al, 2001;Huang et al, 2006;Ntoulia et al, 2006;Wong et al, 2006;Wülfing et al, 2006;Xenidis et al, 2006;Quintela-Fandino et al, 2006), few studies have looked into the relation between CTC and cell-free DNA in this type of cancer (Schwarzenbach et al, 2004). A combined molecular assessment of the circulating DNA and CTC could improve the evaluation of cancer stage and overall prognosis in breast cancer.…”
mentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23] Despite the use of similar PCR-based techniques, the published studies showed a broad range of detection rates of LOH with contradictory results in lung, colorectal and breast cancer patients. 19,20,[24][25][26] Increased concentrations of extracellular DNA have been detected in the plasma from numerous cancer patients 15,27 including PCa patients [28][29][30][31] compared with the low amounts detected in the blood from healthy individuals. The origin of free DNA in blood and BM is still discussed, and it is supposed that free extracellular DNA, which is early released into the blood circulation during the formation of primary tumors, is derived from necrotic and apoptotic cells.…”
mentioning
confidence: 99%
“…These include decreased strand stability (Integrity Index) (51-53), microsatellite alterations (indicating loss of heterozygosity or microsatellite instability) (54,55), epigenetic alterations (gene hypermethylations) (56,57) and presence of specific mutations in oncogenes/tumor suppressor genes [including APC, WNT signaling pathway regulator, KRAS proto-oncogene (KRAS), GTPase, tumor protein p53, phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit αand B-Raf proto-oncogene, serine/threonine kinase (BRAF)] (2,28,41). A recent study on circulating cell free-DNA in colorectal cancer (CRC) showed 100% specificity and sensitivity for the BRAF V600E mutation and 98% specificity and 92 sensitivity for detection of KRAS point mutations (58).…”
Section: Cancer Specific Biomarkersmentioning
confidence: 99%